Vapor-liquid equilibria of acetone-toluene-water system in the presence of sodium chloride and cupric chloride - Pham, Thuy Phuong Thi (Animo Repository, 2005)
The increasing worldwide demand for electronics, semiconductors and optical devices makes these industries expand all over the world especially in Asia. However, the increase in production is coupled with significant increase in the amount of hazardous spent solvents generated such as isopropyl alcohol (IPA), toluene, acetone, methyl ethyl ketone (MEK) and n-methyl pyrolidone (NMP). The spent solvents are wastes from the cleaning processes. They are mixture of solvents that are used to remove adhering dirt, grease and waxes and usually mixed with water in lower quantity. Traditionally, these spent solvents are handled like special wastewater and treated accordingly. However, due to the increasing quantity, it is no longer economically feasible. Traditional distillation is not applicable to these types of mixtures to recover the organic solvents at high purity due to high molecular affinity among these solvents. Another method of separating these solvents by taking advantage of the differences in molecular attraction of the species in the solution in the presence of a strong electrolyte is now being considered. This technique had been successfully applied in many binary systems. However, very few studies were conducted applying this behaviour to ternary and multi-component systems. This prompted researchers to look into the applicability of these theories to mixtures of spent solvents for the possible recovery of each of these solvents. This work determined the vapor-liquidequilibria (VLE) of ternary systems, acetone toluene - water in the absence as well as in the presence of NaCl and CuCl2 using an ebulliometer. The VLE and the normal boiling point of the system acetone toluene - water at unsaturated, saturated and super-saturated concentrations of salt were measured. The amount of water in the initial solution was fixed at 10% and 20%-mole. Results showed that the solutions with NaCl boil at lower temperature than those without salt when the concentration of acetone is greater than 40 mole-%. Theoretically, the lowering of the boiling point is known as positive deviation and this is commercially advantageous. Distillation at lower temperature means substantial amount of energy will be saved making the process more economical. Another interesting finding is the increase in the concentration of the non-polar substance (toluene) in the vapor phase when salt is added. Water, being a polar molecule, is attracted to the salt resulting in the lowering of its vapor pressure. The higher the concentrations of the ions present in solution the greater is the amount of toluene that will separate from the solution. Experimental results proved this hypothesis when at 0.5 molality of NaCl, the amount of toluene in vapor phase is greater than that in the liquid phase. CuCl2, which is less electronegative than CuCl2, also proved to be less effective in reducing the molecular affinity to polar solvents ii (water and acetone) than to non-polar solvent (toluene). This finding opens the possibility of using molecular affinity modification for selective separation technique and can be easily expanded to multi-component system. Distillation of the ternary system in the presence of NaCl and CuCl2 was done to verify the results obtained from the ebulliometer using a laboratory fractionating column set-up. All experiments were performed at total reflux. The amount of water in the initial solution was fixed at 10%-mole. Salts were added into the initial solution at the same molality that was set in the ebulliometer experiments. The results also showed an increase in the amount of toluene in the distillate. The amount of toluene in the distillate increased to a maximum value of 2.46%-mole when NaCl was added compared to 0.28%-mole when no salt was added. The relative separation of acetone/toluene (ad 12) decreased considerably by 71.2% when 0.05m of NaCl was added and by 88.8% when 0.5m of NaCl was added. It was proved that NaCl is more effective than CuCl2 in obtaining more toluene in the distillate as well as reducing the relative separation of acetone/toluene.